2001
DOI: 10.1006/jcph.2001.6822
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Coordinate System for Solving the Three-Dimensional Euler Equations

Abstract: Two general coordinate systems have been used extensively in computational fluid dynamics: the Eulerian and the Lagrangian. The Eulerian coordinates cause excessive numerical diffusion across flow discontinuities, slip lines in particular. The Lagrangian coordinates, on the other hand, can resolve slip lines sharply but cause severe grid deformation, resulting in large errors and even breakdown of the computation. Recently, Hui et al. (J. Comput. Phys. 153, 596 (1999)) have introduced a unified coordinate syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…This includes the Eulerian coordinates as a special case when h = 0 and the Lagrangian one when h = 1. As we have known from Hui's works [10,11], it is shown that the smooth solutions of the system of two-dimensional Euler equations of gas dynamics written in the classical Lagrangian coordinates are equivalent to the same system written in the unified coordinates with h = 1. The steps of the proof can easily be repeated for the current artificial compressibility flow equations to show that its weak hyperbolicity existed on the classical Lagrangian coordinates.…”
Section: Governing Equationmentioning
confidence: 98%
See 1 more Smart Citation
“…This includes the Eulerian coordinates as a special case when h = 0 and the Lagrangian one when h = 1. As we have known from Hui's works [10,11], it is shown that the smooth solutions of the system of two-dimensional Euler equations of gas dynamics written in the classical Lagrangian coordinates are equivalent to the same system written in the unified coordinates with h = 1. The steps of the proof can easily be repeated for the current artificial compressibility flow equations to show that its weak hyperbolicity existed on the classical Lagrangian coordinates.…”
Section: Governing Equationmentioning
confidence: 98%
“…Therefore, numerical diffusion across the slip line can be reduced to a minimum with the crisp capturing of the contact discontinuity. This method was also extended to three-dimensional inviscid flow problems [11] and to shallow water wave problems [12]. In addition, Jin and Xu [13] recently provide another alterative to simulate the low Reynolds number flow based on gas-kinetic BGK model.…”
Section: Introductionmentioning
confidence: 98%
“…The wave corresponding to the eigenvalue = 1 , 2 , 3 , or 4 is called an expansion wave in the wave frame if * /* >0, a compression wave if * /* <0, and a linearly degenerate one if * /* = 0.…”
Section: Propositionmentioning
confidence: 99%
“…Hui and his co-workers [3,4], originally proposed a unified coordinate system which includes the Eulerian approach and Lagrangian approach as two special cases. It keeps the advantages of the Lagrangian approach in capturing sliplines while avoiding severe grid deformation.…”
mentioning
confidence: 99%
“…Recently, Hui and his co-workers proposed a unified coordinate system which unifies both approaches [4,[6][7][8]. This unified approach combines the advantages of the Eulerian approach and the Lagrangian approach.…”
Section: Introductionmentioning
confidence: 99%